Aircraft wing build philosophy change through system pre-equipping of major components - Judt, David M.; Forster, Kevin; Lockett, Helen L.; Lawson, Craig P.; Webb, Philip (Society of Automotive Engineers (SAE), 2016)
In the civil aircraft industry there is a continuous drive to increase the aircraft production rate, particularly for single aisle aircraft where there is a large backlog of orders. One of the bottlenecks is the wing assembly process which is largely manual due to the complexity of the task and the limited accessibility. The presented work describes a general wing build approach for both structure and systems equipping operations. A modified build philosophy is then proposed, concerned with large component pre-equipping, such as skins, spars or ribs. The approach benefits from an offloading of the systems equipping phase and allowing for higher flexibility to organize the pre-equipping stations as separate entities from the overall production line. Its application is presented in the context of an industrial project focused on selecting feasible system candidates for a fixed wing design, based on assembly consideration risks for tooling, interference and access. Further industrial, human and cost factors are discussed to establish project competiveness. The main findings show a potential to reduce assembly time of systems equipping operations by 30% together with a lower ergonomic impact score. The paper also presents design rules derived from the case study towards a system design for a pre-equipping build philosophy. Primarily, cross component interfaces should be avoided as much as possible. Access for phase one structural operations need to be considered as well as major component jig pickup points. To increase system installation independence, layout considerations of components should lead to sufficient access to all components at any installation stage.